Efficacy and safety of stereotactic body radiotherapy for painful bone metastases: Evidence from randomized controlled trials - Wang, Zilan; Li, Longyuan; Yang, Xingyu; Teng, Haiying; Wu, Xiaoxiao; Chen, Zhouqing; Wang, Zhong; Chen, Gang (Frontiers in Oncology, 2022)
Background: Pain relief is one of the main objectives of radiotherapy for cancer patients with bone metastases. Stereotactic body radiotherapy (SBRT) enables precise delivery of a higher dosage to the target area. Several trials have reported comparisons between SBRT and conventional radiotherapy (cRT) in patients with painful bone metastasis. However, the results of those investigations were inconsistent, and no systematic review or meta-analysis has been done till now. Methods: We systematically searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and Clinicaltrials.gov up to May 1, 2022 for relevant studies. Patients with painful bone metastasis who received SBRT or cRT were included. The primary outcome was the patients’ pain response rate at three months. The secondary outcomes included the rate of pain responders at one month and six months, oral morphine equivalent dose (OMED) use, and any adverse events. STATA software 12.0 was used for the statistical analysis. Results: We collected 533 patients’ data from 4 randomized controlled trials (RCTs), there was a significant difference of pain response rate at 3 months between two groups (RR = 1.41, 95% CI: 1.12-1.77, I2 = 0.0%, P = 0.003). However, no significant difference was found in pain response rate at 1 month (RR = 1.19, 95% CI: 0.91-1.54, I2 = 31.5%, P = 0.201,) and 6 months (RR = 1.25, 95% CI: 0.93-1.69, I2 = 0.0%, P = 0.140). OMED consumption was not significantly different in patients treated with SBRT compared with control group (WMD = -1.11, 95% CI: -17.51-15.28, I2 = 0.0%, P = 0.894). For safety outcome, no statistical difference was found between SBRT and cRT (RR = 0.72, 95% CI: 0.46-1.14, I2= 20.1%, P = 0.162). Conclusion: This study shows that for painful bone metastases, patients with SBRT experienced better pain relief 3 months after radiation than patients with cRT, and SBRT did not increase the incidence of adverse events.